STUDENTS PREFERENCE ON MULTIMEDIA MATERIALS FOR EXTENSIVE LISTENING ACTIVITY - Nurhayati Ganinda; Rini Lindawati (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
One of English language skills that widely use multimedia as a teaching medium is listening skills. This is because the most prominent teaching media for this skill is audio media. Meanwhile, audio media can be easily obtained in types of multimedia that have audio and visual elements such as videos, films, songs, games, etc. Apart from these two elements, other elements such as text and images are often found also in multimedia used in teaching listening skills. Teaching extensive listening skills in particular makes extensive use of multimedia in the teaching process. The aim of this research is to determine the type of multimedia chosen by students in extensive listening practice, and explain their reasons for choosing certain type of multimedia. This research use literature review design using content analysis to analyze data from the references. There are three steps applied in the content analysis process, namely data reduction, data display, and verification. Among the five multimedia listening materials used, film clips and documentaries are the materials that are always chosen, while songs are the materials that are least often chosen for extensive listening activities.